Peningkatan Kemampuan Literasi dan Numerasi Siswa melalui Pengenalan Pembelajaran Matematika - Taufik, Azin; Mohamad Riyadi; Anggar Titis Prayitno (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
This community service program is motivated by the low learning motivation of students, which has contributed to poor literacy and numeracy performance in the Computer-Based National Assessment. Literacy and numeracy skills are essential foundations for students’ academic development; however, various evaluations indicate that these competencies remain low due to limited conceptual understanding and the lack of meaningful learning experiences. Introducing mathematics through contextual approaches offers an effective solution, as it helps students grasp concepts concretely, enhances their ability to read information, interpret data, and solve problems. Through this program, educators and university students collaborate to provide engaging learning activities, educational media, and mathematical games that encourage critical thinking, thereby strengthening students’ literacy and numeracy skills sustainably. To address these challenges, on July 23, 2025, a mathematics introduction activity focusing on matrix material was carried out for students at MA Nurul Huda Beringin. The methods used included lectures, discussions, and simulations, while evaluation was conducted afterward to measure students’ mathematical understanding.